Pengaruh Media Pembelajaran Powtoon pada Materi Sel Terhadap Hasil Belajar Peserta Didik Kelas XI Madrasah Aliyah Pesantren Guppi Samata - Ernawati, Ernawati; Rivai, Andi Tenri Ola; Hamansah, Hamansah (Indo-MathEdu Intellectuals Journal, 2024)
This research covers the application of PowToon learning media to improve student learning outcomes in Cell material. The purpose of this study is to determine the influence of the use of PowToon learning media on the learning outcomes of students in the material of Cell XI MA MA Guppi Samata Islamic Boarding School. This study included a pseudo-experiment using a non-equivalent pretest posttest control group design. The population in this study is all students of class XI MA Guppi Samata Islamic Boarding School consisting of 2 classes. The sampling technique in this study is by using the purposive sampling method. The research instrument is in the form of a learning outcome test consisting of 30 multiple-choice questions. Data analysis techniques use descriptive statistics and inferential statistics. The results of the study showed that students who were taught using PowToon learning media had an average learning outcome of 87.36, while students who were taught using Conventional learning media (Biology Package books) had an average learning outcome of 71.3. The results of inferential statistical analysis obtained a sign value for learning outcomes of 0.000, this value shows that sign < α = 0.000 < 0.05 so that H0 is rejected and H1 is accepted. Based on the results of the analysis, it can be concluded that the application of PowToon learning media has an effect on the learning outcomes of students in the Class XI Cell material of Madrasah Aliyah Guppi Samata Islamic Boarding School.